2000
DOI: 10.1111/j.1572-0241.2000.02185.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of Mesalamine (Rowasa) Suppositories in Remission Maintenance of Ulcerative Proctitis

Abstract: The results demonstrate that mesalamine suppositories are efficacious, well tolerated, and safe for the long-term maintenance of remission of ulcerative proctitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…Mesalamine suppositories in doses of 500 mg daily or twice daily are eff ective in maintaining remission with an apparent doseresponse relationship; only 10 % of patients treated with 500 mg twice daily relapsed at 1 year, compared with a relapse rate of 36 % with once daily dosing ( 124,125 ). Mesalamine enemas in doses of 2 -4 g maintained remission when administered daily (78 % eff ective), every other day (72 % eff ective), or even as infrequently as every third day (65 % eff ective) ( 77,78 ).…”
Section: (Evidence A) When All Of These Measures Fail To Maintain Rementioning
confidence: 99%
“…Mesalamine suppositories in doses of 500 mg daily or twice daily are eff ective in maintaining remission with an apparent doseresponse relationship; only 10 % of patients treated with 500 mg twice daily relapsed at 1 year, compared with a relapse rate of 36 % with once daily dosing ( 124,125 ). Mesalamine enemas in doses of 2 -4 g maintained remission when administered daily (78 % eff ective), every other day (72 % eff ective), or even as infrequently as every third day (65 % eff ective) ( 77,78 ).…”
Section: (Evidence A) When All Of These Measures Fail To Maintain Rementioning
confidence: 99%
“…In conclusion, in maintenance treatment, mesalamine suppository treatments were found to be superior to placebo, mesalamine enema treatment was found to be superior to mesalamine oral treatment, and combined treatment (oral + rectal) was found to be superior to oral treatment (1,(12)(13)(14)17,18). Budesonide enema was not found to be effective in maintenance treatment (15).…”
Section: Resultsmentioning
confidence: 91%
“…A recent Cochrane review reported that sulfasalazine was superior in the maintenance setting [69]. A recent meta-analysis including seven randomized-controlled trials (n = 555 patients) showed that topical mesalazine was effective in preventing relapse of distal UC [12,70]. In the study, 500 mg mesalazine b.i.d.…”
Section: Maintenance Treatmentmentioning
confidence: 99%